Involuntary wellness programs: the case of a large US company. Issue 1 (7th April 2015) - Secchi, Davide; Bui, Hong T.M.; Gamroth, Kathleen
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate recent healthcare reform in the USA, which allows insurance companies to proactively intervene in improving the long-term health of employees, by providing wellness programs as part of their benefits package. Design/methodology/approach – The authors present and analyze data on how employees of a large US Midwest "media and education" company (n=154) perceive economic incentives toward well-being. Data are collected using survey methods and analyzed with a logistic regression. Findings – This study suggests that fairness, accessibility, intention to switch to a healthier lifestyle and desire to see more health-related initiatives affect the way employees seek to participate in the new involuntary wellness programs. By contrast, satisfaction, participation, and income to not affect how these new programs are perceived. Research limitations/implications – These findings suggest that human resource managers should pay attention to employees who are not active in existing wellness programs, and provide support during the transition toward the new involuntary programs, to avoid potential frustration, demotivation, disengagement and, ultimately, decreasing performance among employees. Originality/value – The study is among the first to analyze involuntary wellness programs in the USA, and it provides a basis on which to expand further studies. This research contributes to support the idea that employee wellness is unlikely to be enforced by rule or policy.